Study of Water Flow Behavior in a Saturated Zone - Cuieiras Biological Reserve, Central Amazon - Bastos, Alexandre Souza; Monteiro, Maria Terezinha Ferreira; Ferreira, Sávio José Filgueira; de Oliveira, Regison Costa; Negrón-Juárez, Robinson; Tomasella, Javier; Gastmans, Didier [UNESP]; Teixeira, Vinícius Metrado; de Almeida, Claudenilson Nogueira; Brito, Alderlene Pimentel (Revista Brasileira de Geografia Fisica, 2023)
Underground flow studies from high to low altitudes in the Amazon region, in natural environments, regarding base flow density, are incipient knowledge and do not reflect your current conversation related to water dynamics at different topographic levels. The objective of this work was to analyze the behavior of the water table level in plateau, slope and lowland areas and to obtain a hydraulic conductivity in the saturated zone to estimate the local base flow. The study was carried out in the Cuieiras Biological Reserve in the Central Amazon, north of the city of Manaus. The methodology consisted of collecting hydrological data and using the “slug test” technique in piezometers to determine the saturated hydraulic conductivity. The result demonstrates average values of saturated hydraulic conductivity with a minimum and maximum variation of 30mm/h of 1177 mm/h. Over the years, in the shallows, the water table level, there was a predisposition to variation in a frequency of 0.10 m to 0.60 m; on the slope from 3 m to 5 m and on the plateau from 23 m to 42 m deep. The average base flow obtained was 3.62E-06 m3/s, there was no significant seasonal variation in the base flow in the observed period from 2003 to 2019. It is considered important to explore this result in the characterization of complementary works involving transmissivity, underground solute transport and free aquifer recharge according to topographic sequences in the region. The study contributed with new hydrogeological information, which helps to understand the hydrological processes in a given area.
Estudo do Comportamento do Fluxo de Água em Zona Saturada - Reserva Biológica do Cuieiras, Amazônia Central
Keywords: saturated hydraulic conductivity and groundwater flow velocity; Spatiotemporal water table variability